Penerimaan Minat Penggunaan Central Bank Digital Currency (CBCD) di Kalangan Generasi Z : Studi Kasus pada Mahasiswa FEB Universitas Katolik Widya Mandira Kupang - Lian, Yohanis Pemandi; Lonak, Putri Debora; Bere, Sarlina Agustin Motu; Suban, Maria Petrosia Peni (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This research aims to understand the level of acceptance and interest in using Central Bank Digital Currency (CBDC) among Generation Z, especially students at the Faculty of Economics and Business (FEB) Widya Mandira Catholic University, Kupang. The method used is a qualitative method with a phenomological approach. This research explores perceptions, knowledge, and factors that influence students' interest in using CBDC as a digital currency innovation issued by the central bank. Data was collected through semi-structured in-depth interviews and through Focus Group Discussions (FGD) with a number of students from the Faculty of Economics and Business (FEB). The research results show high acceptance of the Central Bank Digital Currency (CBDC) among generation Z, especially students at the Faculty of Economics and Business (FEB) Widya Mandira Catholic University, Kupang, especially because of the convenience, security and efficiency offered by CBDC in digital financial transactions. The research results also show factors that influence interest in using Centarl Bank Digital Currency (CBDC).